PENGARUH PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE PADA MATA PELAJARAN SEJARAH UNTUK MENUMBUHKAN KARAKTER TANGGUNG JAWAB SISWA DI SMA NEGERI 2 KRAKATAU STEEL CILEGON - Utami Hadiyanti; Tubagus Umar Syarif Hadi Wibowo; Mohammad Ali Fadillah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to examine the effect of the value clarification technique learning model on increasing the character of student responsibility in history subjects at SMA Negeri 2 Krakatau Steel Cilegon for the 2022-2023 academic year. This study uses a quasi-experimental design with nonequivalent control group. Purposive sampling was used during the sampling process. The sample of this research is the experimental class with 35 students and the control class with 34 students. The results of the data analysis show that the development of the character of student responsibility is different between the value clarification technique model and the contextual learning model. Based on the results of the t-test, data were obtained for Tcount = -3.285 and Ttable = 1.667 and a significance threshold of 0.05 indicating that there was an average difference between the experimental and control groups. Thus it can be said that the application of the value clarification technique learning model at SMA Negeri 2 Krakatau Steel Cilegon for the 2022-2023 academic year will support the improvement of students' responsible character in history subjects.